Peningkatan Keandalan Sistem Tenaga Listrik 20 Kv Pekanbaru Dengan Analisa Kontingensi ( N-1 ) - Ishak Erawadi Barutu; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
To a give reliable service, the power system must remain intact and able to cope with various problems that may occur. Thus is something that is very important to plan a good the when system under normal circumstances and contingency or release of an element, the system remains able to distribute electrical energy in a good state.In this study discussed contingency analysis (loss of one of the elements) on the 20kv power system. Contingency analysis which is based on the release of the transformer. Results analysis is used to look at the critical loading or experiencing overload. From the simulation results ETAP 12.6 is known that while contingency 1 in the substation garuda sakti when the transformer 1 out the transformers 2, transformers 3 and transformer 4 will be overloaded as big as 48.8 MVA, 48.8 MVA and 58.8 MVA. Contingency 4,that is the out of the transformer 4 the transformer 1, transformer 2 and 3 transformer overload of 55.7 MVA, 46.5 MVA and 46.5 MVA. At the substation teluk lembu contingency 2 transformer 4 off the generator 6 will overload 133.5%. contingency 3 out of the transformer 7, the transformer 11 overload 114.3%. Generator 7 and the generator 6 overload 129.3% and 104.7%. To cope the overload then made two solutions that load shedding and connection coupling.Keywords: analysis contingency, reliability